Longitudinal Associations Between Pain and Psychosocial Adjustment in Youth With Spina Bifida. (1st June 2020) - Ohanian, Diana M; Murray, Caitlin B; Shirkey, Kezia C; Wartman, Elicia C; Winning, Adrien M; Stiles-Shields, Colleen; Ramirez, Sonia B; Holmbeck, Grayson N
Abstract: Objective: This study examined: (a) the nature and prevalence of pain in youth with spina bifida (SB) (b) common coping responses to pain, and (c) longitudinal, bi-directional associations between internalizing symptoms and pain characteristics. Methods: Data were collected from youth ( N  = 140, 53.6% female, ages 8–15 at Time 1) and their parents and teachers at two time points spaced 2 years apart. Youth reported on several pain characteristics and coping responses. Multiple informants reported on child internalizing symptoms. Evaluation of Aims 1–3 was based on descriptive analyses, bivariate correlations, and linear and logistic regressions. Results: About 25% of the sample reported chronic pain (e.g., experiencing pain one or more times per week over the past 3 months) at Time 1 or 2, with roughly one-third of this chronic pain subsample reporting chronic pain both time points. Pain was usually rated as mild in intensity for the full sample and most commonly experienced in the head, abdomen, and back, and described as "aching." Youth with chronic pain reported significantly higher pain intensity and tended to use condition-specific methods to cope with pain (e.g., taking off braces). In 2 of 10 analyses, internalizing symptoms at Time 1 were associated with chronic pain and pain intensity at Time 2. Conclusions: Roughly one-fourth of youth with SB are at risk for experiencing chronic pain, highlighting the need for increased assessment and treatment of pain in this population. Youth psychological functioning appears to more often precede, rather than being a consequence of pain symptoms.